2021
DOI: 10.3389/fimmu.2021.613893
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Air Pollution and the Risk of Uveitis: A Nationwide, Population-Based Cohort Study

Abstract: Previous studies have revealed an association between ocular surface disorders and air pollution, few studies have focused on the risk of uveitis. We aimed to investigate whether air pollution increases the risk of uveitis. We used the Taiwan Longitudinal Health Insurance Database (LHID) and the Taiwan Air Quality Monitoring Database (TAQMD) to conduct a retrospective cohort study. Air pollutant concentrations, including those of carbon dioxide (CO2), were grouped into four levels according to quartiles. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Regarding environmental cigarette smoke exposure, a case-control study showed increased risks of neovascular and atrophic AMD [107]. However, in the Blue Mountains Eye Study, Smith and associates found that passive smoking does not significantly increase the risk for late AMD [108]. Cigarette vapor was reported to accelerate the progression of inflammation and angiogenesis in the retina of mice, which were possibly associated with the onset of wet AMD [109].…”
Section: Retinal and Macular Diseasesmentioning
confidence: 99%
“…Regarding environmental cigarette smoke exposure, a case-control study showed increased risks of neovascular and atrophic AMD [107]. However, in the Blue Mountains Eye Study, Smith and associates found that passive smoking does not significantly increase the risk for late AMD [108]. Cigarette vapor was reported to accelerate the progression of inflammation and angiogenesis in the retina of mice, which were possibly associated with the onset of wet AMD [109].…”
Section: Retinal and Macular Diseasesmentioning
confidence: 99%
“…Second, the participants in our study were predominantly Taiwanese; therefore, the effects of different races and ethnicities could not be assessed. Third, we used the ICD-9 coding (Outpatient visits≧ 3 or ≧1 inpatient) as the basis for a diagnosis of uveitis, which have used in several studies (49)(50)(51). After literature review, one Hawaii's study reported that the positive predictive value (PPV) of ICD-9 codes for identifying individual uveitis codes ranged from 0% to 100% and the overall PPV was 61%.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwanese researchers use an anonymous identification number to link each registry data and related medical information for academic purposes. Recently, some studies also used LHID to investigate public health issues [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%